2011
DOI: 10.1002/poc.1943
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation and IR spectroscopic characterization of 3,5‐difluoropyridyl‐2,4,6‐trinitrene

Abstract: The photochemistry of 2,4,6-triazido-3,5-difluoropyridine 21 was investigated by matrix infrared and electron paramagnetic resonance spectroscopies. Ultraviolet irradiation (>260 nm) of 21 results in the formation of 3,5-difluoropyridyl-2,4,6-trinitrene 26 in yields high enough for characterization by infrared spectroscopy. The experimental infrared spectrum is in good agreement with density functional theory calculations. Under similar conditions, a very strong electron paramagnetic resonance spectrum of sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 52 publications
(69 reference statements)
4
25
0
Order By: Relevance
“…The present 15 N NMR spectroscopic study confirmed that none of triazides 1–7 and 10 displays any signals between δ +50 and −90 ppm that can be assigned to isomeric tetrazoles. These data agree well with the results of previous 13 C NMR spectroscopic studies of triazides 1–7 and 10 …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The present 15 N NMR spectroscopic study confirmed that none of triazides 1–7 and 10 displays any signals between δ +50 and −90 ppm that can be assigned to isomeric tetrazoles. These data agree well with the results of previous 13 C NMR spectroscopic studies of triazides 1–7 and 10 …”
Section: Resultssupporting
confidence: 93%
“…When aromatic polyazides have two or more nonequivalent azido groups, these groups can selectively react with dipolarophiles, electrophiles, nucleophiles and reductants or undergo selective thermolysis and photolysis . Recently, we have reported the synthesis and some chemical transformations of triazides 1–6 (Scheme ) . It was found that, upon UV irradiation, triazides 2 and 3 undergo selective photolysis of the α ‐azido groups to form the corresponding quintet 2,6‐dinitrenopyridines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, previous EPR studies have shown that irradiation of triazide 1a with light at λ = 313 nm selectively gave quintet dinitrene 4a as the major intermediate product (Scheme 1) [78]. Most recently, a similar selectivity was observed during the photolysis of triazide 1b where quintet dinitrene 4b was the major intermediate product (Scheme 1) [9]. By contrast, the photolysis of triazide 7 occurs selectively on the azido group located on the γ-phenyl ring, yielding dinitrene 9 as a single quintet intermediate (Scheme 1) [10].…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have shown that parent 2,4,6-triazido-3,5-difluoropyridine and 2,4,6-triazido-3,5-dichloropyridine also underwent selective photolysis of the azido groups to form corresponding quintet pyridyl-2,6-dinitrenes as the major intermediate products. 25,26 Based on these analogies, we assigned the product with |D q1 | = 0.289 cm −1 and |E q1 | = 0.0571 cm −1 to quintet dinitrene Q-1 (Scheme 1).…”
Section: A Esr Studiesmentioning
confidence: 99%